2019
DOI: 10.5935/0103-507x.20190012
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors, and outcomes of unplanned extubation in adult patients in a resource-limited teaching hospital in the Philippines: a cohort study

Abstract: Objective We aimed to determine the incidence, risk factors, and outcomes of unplanned extubation among adult patients. Methods We conducted a prospective cohort study of adult intubated patients admitted to the charity wards of a government tertiary teaching hospital in the Philippines. Patients managed in both intensive care and nonintensive care settings were included. Patients were followed-up until discharge or until seven days postextubation. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
2
11
1
Order By: Relevance
“…In this study, the magnitude of unplanned extubation was 19.74% which was in the range of 0.5%–35.8% reported in the systematic literature review [ 10 ]. The result we found on the magnitude of unplanned extubation was in line with the study which was done in the Philippines, unplanned extubation rate of 19% [ 9 ], and the research done in Taiwan with an incidence rate of 22.5% [ 17 ]. On the other hand, the result was inconsistent with research done in British (4.47%), Belgium (4.2%), and Spain (10%) [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, the magnitude of unplanned extubation was 19.74% which was in the range of 0.5%–35.8% reported in the systematic literature review [ 10 ]. The result we found on the magnitude of unplanned extubation was in line with the study which was done in the Philippines, unplanned extubation rate of 19% [ 9 ], and the research done in Taiwan with an incidence rate of 22.5% [ 17 ]. On the other hand, the result was inconsistent with research done in British (4.47%), Belgium (4.2%), and Spain (10%) [ 18 ].…”
Section: Discussionsupporting
confidence: 89%
“…The possible reason for this Addis Ababa governmental hospitals are the area of trainee and was loaded with junior resident which has a significant contribution to the incidence of unplanned extubation evidenced by our data. This was supported by the research done in Egypt in 2019 patients managed by junior residents were more likely to increase the probability of unplanned extubation [ 9 ]. The other reason most of them used a case-control study design,cross-sectional study design, they were get secondary data from previous records which has the chance of losing the case.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…required reintubation. Moreover, Phoa et al 9 found that the rate of reintubation after failed UE was 58.3%, out of which 71.4% had immediate reintubation, and Uy et al 12 reported that reintubation was necessary for 61.1% of patients with UE, which was much higher than in patients with planned extubation (25.4%). In a review by Bambi et al,23 the reintubation rate ranged from 1.81% to 88%.…”
Section: What This Paper Addsmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Not every patient who had UE has failed extubation but failed UE requiring reintubation could be associated with several adverse events, such as aspiration pneumonia, bronchospasm, arrhythmia, respiratory failure, or even sudden cardiac arrest. [10][11][12][13][14] Moreover, patients who had UE may be required to prolong their hospital or ICU stay and MV duration. [14][15][16][17][18] Most importantly, UE can adversely affect the patients' survival rates.…”
mentioning
confidence: 99%